PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 26 LUBUKLINGGAU - Bela Agustina; Akmal Rijal; Asep Sukenda Egok (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether the application of the Make A Match learning model can improve the science learning outcomes of fourth-grade students at SD Negeri 26 Lubuklinggau. This research method used an experimental research method with a pre-test and post-test experimental design. Sampling was taken using a purposive sampling technique, considering that the population consisted of two classes. The sample in the study was 25 students of class IV.A. The instrument used by the researcher was a multiple-choice questionnaire with 15 questions. Data collection was carried out using a test technique. Data were analyzed using the t-test formula. Based on the results of the hypothesis test, the calculated t_value is then consulted with the t_(table) in the t distribution list with a significance level of α = 0.05 so that the calculated t_value> t_table (3.551> 1.714) is obtained. With this, H_0 is rejected and H_a is accepted. So it can be concluded that the Make A Match learning model can complete the science learning outcomes of fourth-grade students of SD Negeri 26 Lubuklinggau.